Effects of MWCNTs on the Tensile Properties and Thermal Conductivity of BaTiO3 /Epoxy Nanocomposites - Nassif, Iman Ibrahem; Al-Shabander, Ban Mazin (Iraqi Journal of Science, 2020)
This research studied the effects of modified BaTiO3 (BT) nanoparticles with coupling agent γ-APS (0.5wt. %) on the tensile and thermal conductivity of epoxy nanocomposites with respect to content (0.25, 0.5, 0.75, 1, 3 and 5wt. %). Multiwall carbon nanotubes (MWCNTs) at different concentration (0.2, 0.4, 0.8 and 1 wt. %) were added to the BaTiO3/epoxy nanocomposites. The influence of MWCNTs on the tensile properties and thermal conductivity was investigated. The tensile strength and Young’s modulus of BaTiO3/epoxy nanocomposites film were increased at up to 3 wt. % of added BT, but adding BT at more than 3 wt.% decreased the strength of epoxy. The tensile strength was increased with increasing MWCNTs content from 32 MPa for pure epoxy to the value 56.8 MPa for 1wt. % of MWCNTs content. The thermal conductivity of BaTiO3/epoxy nanocomposites improved with increase of BT content. At 3wt. % and 5wt. % of BaTiO3 the thermal conductivity of nanocomposites decreased. The increase of MWCNTs concentration from 0.2 wt. % to 1 wt. % resulted in a thermal conductivity enhancement.